Antimicrobial Efficacy of Intracanal Medicaments against E. Faecalis Bacteria in Infected Primary Molars by Using Real-Time PCR: A Randomized Clinical Trial - Yasamin Ghahramani; Najmeh Mohammadi; Ahmad Gholami; Dordaneh Ghaffaripour (International Journal of Dentistry)
Aim. This study aimed to compare the antimicrobial efficacy of calcium hydroxide (CH) and triple antibiotic paste (TAP) against E. faecalis bacteria in infected primary molars. Methods and Materials. Thirty-nine 4–6-year-old children with an infected primary molar were randomly divided into three equal groups (n = 13) to receive either CH or TAP and an untreated control group. Following access cavity preparation, the first microbiological samples (S1) were collected by using absorbent paper points. The canals were prepared and rinsed. Then, CH or TAP was applied in the root canals. Seven days later, the second microbiological samples (S2) were collected. DNA extraction was performed to count E. faecalis bacteria by using real-time PCR for S1 and S2 samples. Data were analyzed through one-way ANOVA and Tukey’s test (α = 0.05). Results. E. faecalis bacteria counts decreased significantly in CH and TAP groups compared with the control group (P≤0.001). However, no statistically significant difference existed between these two groups (P=0.698). Conclusion. Both TAP and CH have significant antimicrobial effects as intracanal medicament between the treatment sessions in infected primary teeth.